From Undetectable Equals Untransmittable (U=U) to Breastfeeding: Is the Jump Short? - Tullio Prestileo; Sanfilippo Adriana; Di Marco Lorenza; Antonina Argo (MDPI AG, 2022)
Background: Vertical transmission of HIV infection may occur during pregnancy, at childbirth or through breastfeeding. Recommendations on the safety of breastfeeding of HIV-infected women on effective antiretroviral treatment are not univocal among international guidelines (WHO 2010, EACS 2017, DHHS 2017), leaving space for variability at the patient's level. Methods: We collected clinical, laboratory and outcome data from 13 HIV-infected pregnant women who, between March 2017 and June 2021, elected to breastfeed their children against specific medical advice. All mothers were on antiretroviral therapy with darunavir or raltegravir plus emtricitabine/tenofovir disoproxil and remained HIV-RNA undetectable and >400 cells/mmc CD4+ lymphocytes during pregnancy and breastfeeding. Prophylactic antiretroviral therapy (zidovudine for 4 weeks) was started immediately after birth in all newborns. The mean duration of breastfeeding was 5.4 months. Newborns were tested for HIV-RNA multiple times: at birth, 1, 3, and 6 months after birth, and 1, 3 and 6 months after the end of breastfeeding. Results: None of the infants were infected by HIV. Conclusions: Our experience, gathered in the setting of freedom of choice on the patient's side, while insufficient to address the eventual safety of breastfeeding in HIV-infected mothers since the represented cohort is numerically irrelevant, supports the extension of the U=U (Undetectable Equals Untransmittable) paradigm to this setting. Since breastfeeding is often requested by women with HIV planning pregnancy, more extensive comparative studies should be performed.